1995
DOI: 10.1111/j.1151-2916.1995.tb08235.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of SiC‐Fiber‐Reinforced Si3N4 Composites at Ambient and Elevated Temperatures

Abstract: The crack growth behavior in unidirectional SiC‐fiber‐rein‐forced Si3N4‐matrix composites fabricated in our laboratories was investigated as a function of fiber volume fraction and temperature. Both the stress‐intensity factor and an energy approach were adopted in the characterization of the crack growth behavior. Crack resistance increased with crack extension (R‐curve or T‐curve) as a result of bridging effects associated with the intact fibers. Large‐scale bridging was observed, and was considered in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With the unit of A being J (Joules), the unit of WOF (or fracture resistance) is J/m 2 or more conveniently, kJ/m 2 [20,21]. Eight specimens, approximately 25 mm in length, 2 mm in width and thickness were prepared and tested.…”
Section: Flexural Strength Elastic Modulus and Work Of Fracturementioning
confidence: 99%
“…With the unit of A being J (Joules), the unit of WOF (or fracture resistance) is J/m 2 or more conveniently, kJ/m 2 [20,21]. Eight specimens, approximately 25 mm in length, 2 mm in width and thickness were prepared and tested.…”
Section: Flexural Strength Elastic Modulus and Work Of Fracturementioning
confidence: 99%
“…where A is the area under the load-displacement curve, which is the work done by the applied load to deflect and fracture the specimen. With the unit of A being J (Joules), the unit of WOF (or fracture resistance 40 ) is J/m 2 or more conveniently, kJ/m 2 (k = 10 3 ). 30,39 After the matrix had cracked, most of the fiber-reinforced specimens were still intact, due to fibers bridging the cracks and supporting the applied load.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Second-phase inclusions of various shapes have been tested in Si 3 N 4 , such as particles, 12 fibers, 13,14 whiskers, [15][16][17][18][19][20][21][22] and platelets, 1,[23][24][25][26][27][28][29] most of which were made of SiC. A beneficial effect of fibers and whiskers on the fracture toughness at ambient temperature was found in some cases; 14,15,21 however, in most of the investigations, no increase in strength or even a strength degradation was observed. 19,21 The only exception is the work of Buljan et al, 15 who reported a 25% strength increase due to whiskers.…”
Section: Introductionmentioning
confidence: 99%